2017
DOI: 10.1021/acs.langmuir.7b02654
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Membrane Properties of Oxidized Ceramide Derivatives

Abstract: Ceramide is a bioactive lipid with important roles in several biological processes including cell proliferation and apoptosis. Although 3-ketoceramides that contain a keto group in place of the 3-OH group of ceramide occur naturally, ceramide derivatives oxidized at the primary 1-OH group have not been identified to date. To evaluate how the oxidative state of the 1-OH group affects the physical properties of membranes, we prepared novel ceramide derivatives in which the 1-OH group was oxidized to a carboxylic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…Surface pressure π of the Cer monolayers increased as the monolayers were laterally compressed and then reached a plateau at their collapse pressures (π > 50 mN/m). The π– A isotherm of the Cer monolayer is similar to that in the previous reports. , Then, we determined the molecular occupied areas of Cers at 20 mN/m ( A 20 ) from the π– A isotherms and found that the A 20 values of CerNHAc and CerN 3 are larger than that of Cer (Figure b). This result is reasonable because CerNHAc and CerN 3 have larger headgroups than Cer.…”
Section: Results and Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Surface pressure π of the Cer monolayers increased as the monolayers were laterally compressed and then reached a plateau at their collapse pressures (π > 50 mN/m). The π– A isotherm of the Cer monolayer is similar to that in the previous reports. , Then, we determined the molecular occupied areas of Cers at 20 mN/m ( A 20 ) from the π– A isotherms and found that the A 20 values of CerNHAc and CerN 3 are larger than that of Cer (Figure b). This result is reasonable because CerNHAc and CerN 3 have larger headgroups than Cer.…”
Section: Results and Discussionsupporting
confidence: 80%
“…As discussed above, the weakened domain formability of CerNH 2 can be accounted for by the formation of CerNH 3 + in water. In addition, we previously reported that an anionic Cer-analogue CerCOO – has lower domain formability than the neutral Cer-analogues in POPC and SM bilayers . Taken together, we can conclude that the electrostatic repulsion between Cers reduces their domain formation, irrespective of the positive or negative charge.…”
Section: Results and Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Cer lacks the headgroup typical of phospholipids or glycosphingolipids and generally possesses two hydroxy groups at the C1 and C3 positions. Recently, in order to study how the oxidative state of the primary alcohol group of Cer affects membrane physical properties, we prepared Cer derivatives in which the primary alcohol group was oxidized to a carboxylic acid and methylester (PCerCOOH and PCerCOOMe, Figure ) and examined how the oxidative state of the primary alcohol of Cer influences membrane physical properties . As a result, both derivatives exhibited membrane properties similar to those of native Cer.…”
Section: Introductionmentioning
confidence: 99%